Análise semiótica de narrativas de mulheres - professoras - aposentadas do norte do Tocantins: - Ferreira, Érica de Cássia Maia (2023)
This thesis analyzes the life stories and formation of retired female teachers residing in Tocantins. It’s an interdisciplinary study guided by Oral History, Discursive Semiotics, and studies on women's history. The objective was to investigate the life histories of retired teachers who worked in the northern part of Tocantins in order to record their academic and teaching experiences, as well as retirement, as their stories contribute to the educational history of the region. We interviewed ten retired female teachers, six of whom worked in the municipality of Araguatins and four in Araguaína. The fact that we developed an interdisciplinary study allowed us to understand memory in its various meanings, the transformations experienced by female teacher subjects in relation to other subjects and objects. We adopted the semi-structured interview as a data production instrument, using two resources: audio and video-audio. Considering that the generative path of meaning allows us to identify the relationship between subjects and between subjects and objects (BERTRAND, 2003, p. 286), and their transformations implied by lived events, we related the structuring categories of the interviews to the semiotic categories of competence, performance, and sanction, to compose the analysis sections. For the analysis, we intertwined the life stories of the narrators, considering the regularities and singularities present in the narratives that reveal the retired female teachers as